2001
DOI: 10.1073/pnas.181213498
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of MEK inhibitor U0126 affords brain protection against forebrain ischemia and focal cerebral ischemia

Abstract: Brain subjected to acute ischemic attack caused by an arterial blockage needs immediate arterial recanalization. However, restoration of cerebral blood flow can cause tissue injury, which is termed reperfusion injury. It is important to inhibit reperfusion injury to achieve greater brain protection. Because oxidative stress has been shown to activate mitogen-activated protein kinases (MAPKs), and because oxidative stress contributes to reperfusion injury, MAPK may be a potential target to inhibit reperfusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
291
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(319 citation statements)
references
References 38 publications
25
291
2
1
Order By: Relevance
“…High-mobility group box 1 proinflammatory signaling might begin early, possibly in the first hour after focal ischemia, but may continue for hours thereafter (Faraco et al, 2007). Consistent with a more protracted HMGB-1 signaling, we have previously reported neuroprotection through ERK inhibition, even when the treatment had been initiated 3 h after MCAO (Namura et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…High-mobility group box 1 proinflammatory signaling might begin early, possibly in the first hour after focal ischemia, but may continue for hours thereafter (Faraco et al, 2007). Consistent with a more protracted HMGB-1 signaling, we have previously reported neuroprotection through ERK inhibition, even when the treatment had been initiated 3 h after MCAO (Namura et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…The effect of MEK1/2 inhibition on infarct volume has been studied by Namura and colleagues. However, they used a different species (mouse), time point (7 days) and did not examine the cerebral vasculature (Namura et al 2001). In the present study, the question of whether the decrease of the infarct volume is a direct effect of MEK1/2 inhibition in neurons or a more indirect effect due to the normalization of the vascular receptor responses remains to be answered.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have shown an involvement of the MEK/ERK1/2 signalling pathway in focal cerebral ischaemia, and inhibitors towards this pathway are able to diminish the ischaemic area (Alessandrini et al 1999;Namura et al 2001). In addition, Lennmyr and colleagues showed that ERK1/2 is activated in both the ipsilateral and contralateral cerebral blood vessels (Lennmyr et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of 12-Otetradecanoylphorbol-13-acetate-induced ear edema, topical administration of U0126 effectively blocked both swelling and tissue ERK phosphorylation (44). When administered intravenously, U0126 blocked IL-1␤ production and focal ischemic injury in mice (45), as well as the inflammation associated with cisplatin-induced renal injury (46).…”
Section: Discussionmentioning
confidence: 99%